2010
DOI: 10.1007/s11340-010-9417-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Methods for Exact Subpixel Shifting

Abstract: An approach to quantifying the errors in digital image correlation (DIC) is presented using experimentally produced images. The challenge arises in creating exact subpixel shifted images in an experiment. This was accomplished via numerical binning of an ultra-high resolution image. The shifted images are then used for a preliminary analysis of 2D correlation software uncertainty and investigation of speckle pattern quality. Because it is often necessary to use numerically shifted images, for uncertainty quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 13 publications
0
76
0
Order By: Relevance
“…In [23] a method for producing high-precision experimentally subpixel shifted images has been created. The author [23] produced a set of speckle patterns shifted with a step of 0.1 pixels.…”
Section: Testing the Methods Of Speckle Pattern Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [23] a method for producing high-precision experimentally subpixel shifted images has been created. The author [23] produced a set of speckle patterns shifted with a step of 0.1 pixels.…”
Section: Testing the Methods Of Speckle Pattern Correlationmentioning
confidence: 99%
“…In [23] a method for producing high-precision experimentally subpixel shifted images has been created. The author [23] produced a set of speckle patterns shifted with a step of 0.1 pixels. There are available two sets of speckle patterns with high and low contrast [24] which are used in the current work for determining the accuracy of the algorithm.…”
Section: Testing the Methods Of Speckle Pattern Correlationmentioning
confidence: 99%
“…In particular, the rigid motion of the structure is simulated by phase shifting the Fourier Transform of the image of the target in equilibrium position [26]. Simultaneously motion blur is generated using the averaging algorithm [27].…”
Section: Simulating Image Formationmentioning
confidence: 99%
“…In this particular case, stereoscopic images are captured at a frame rate of 5 fps during the heating, sagging and bubble inflation phase and correlated in the 3D module of the academic correlation software MatchID (http://www.matchid.org). This software was benchmarked to the results of commercial systems [10] and it was found that for the bias, MatchID is in an identical range as VIC (Correlated Solutions (http://www.correlatedsolutions.com)) whereas an improved lower standard deviation by a factor of four was achieved. The correlation results in a full field displacement and strain map.…”
Section: Digital Image Correlation In Thermoformingmentioning
confidence: 99%